2013
DOI: 10.1260/0263-6174.31.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Zn12O12 Fullerene-like Cage as a Potential Sensor for SO2 Detection

Abstract: A computational study based on density functional theory calculations was performed to investigate the potential possibility of using Zn 12 O 12 fullerene-like cage as an electronic sensor for SO 2 detection. For adsorption of SO 2 on the Zn 12 O 12 nanocage, three stable configurations were identified. The energy gap of Zn 12 O 12 nanocage is very sensitive to the presence of SO 2 molecule. The energy gap decreases from 4.19 eV in the free nanocage to 1.88 eV in the SO 2-adsorbed form. This phenomenon increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Ghenaatian et al [35] investigated the Zn 12 O 12 nanocage as a promising adsorbent and detector for CS 2 . Baie et al examined the Zn 12 O 12 fullerene-like cage as a potential sensor for SO 2 detection [36]. Ammar [37] reported that the Zn 12 O 12 nanocage is a potential sorbent and detector for formaldehyde molecules.…”
mentioning
confidence: 99%
“…Ghenaatian et al [35] investigated the Zn 12 O 12 nanocage as a promising adsorbent and detector for CS 2 . Baie et al examined the Zn 12 O 12 fullerene-like cage as a potential sensor for SO 2 detection [36]. Ammar [37] reported that the Zn 12 O 12 nanocage is a potential sorbent and detector for formaldehyde molecules.…”
mentioning
confidence: 99%
“…Therefore, the Ag-decorated ZnO nanocage has the potential to convert CO 2 gas directly into electrical signals and can therefore be used in CO 2 sensors. 60…”
Section: Resultsmentioning
confidence: 99%
“…ZnO is a semiconducting metal oxide that has been widely used as sorbent, gas sensor, corrosion protector, catalyst/catalyst support, et al It is safe, stable and cheap, making it popular in various practical applications. It is a common sorbent in industry to remove SO 2 and the component of catalysts used in many petroleum related process. Due to this fact, a lot of studies focusing on the SO 2 interaction with ZnO were conducted in the last few decades.…”
Section: Introductionmentioning
confidence: 99%